Answer:
1. [tex](\sqrt[5]{(m+2)})^{3} = (m+2)^{\frac{3}{5}}[/tex]
2. [tex](\sqrt[3]{(m+2)})^{5} = (m+2)^{\frac{5}{3}}[/tex]
3. [tex]\sqrt[5]{(m)}^{3}+2 = m^{\frac{3}{5}}+2[/tex]
4. [tex]\sqrt[3]{(m)}^{5}+2 = m^{\frac{5}{3}}+2[/tex]
Step-by-step explanation:
Recall that
[tex](\sqrt[n]{x})^{m} = (x^{\frac{m}{n}})[/tex]
Where [tex]x^{m}[/tex] is called radicand and n is called index
1. Root(5, (m + 2) ^ 3)
In this case,
n is 5
m is 3
x = (m + 2)
[tex](\sqrt[5]{(m+2)})^{3} = (m+2)^{\frac{3}{5}}[/tex]
2. Root(3, (m + 2) ^ 5)
In this case,
n is 3
m is 5
x = (m + 2)
[tex](\sqrt[3]{(m+2)})^{5} = (m+2)^{\frac{5}{3}}[/tex]
3. Root(5, m ^ 3) + 2
In this case,
n is 5
m is 3
x = m
[tex]\sqrt[5]{(m)}^{3}+2 = m^{\frac{3}{5}}+2[/tex]
4. Root(3, m ^ 5) + 2
In this case,
n is 3
m is 5
x = m
[tex]\sqrt[3]{(m)}^{5}+2 = m^{\frac{5}{3}}+2[/tex]